(untitled) (Journal of human and social sciences, 2016)
This paper aims to clarify the nature of the relationship between theory and method in social research, drawing on the scientific foundations laid by Ibn Khaldun in the 14th century, who is considered the founding father of sociology through his development of observation and the study of social phenomena. These efforts were later advanced by Western thinkers such as Auguste Comte, Durkheim, Weber, and others, eventually evolving into the contemporary form of organized scientific explanation supported by modern statistical and technological tools. The study demonstrates that theory represents the logical aspect of scientific research, while method embodies the empirical side associated with observation and measurement. Through the interaction of theory and method, scientific knowledge emerges, contributing to the explanation of social phenomena and the understanding of relationships among variables. The paper also discusses deductive and inductive models in social research, highlighting the interactive and complementary nature of theory and method, where theory is used to generate hypotheses and method provides the tools to test or refine them. The paper concludes that the relationship between theory and method is neither linear nor separate, but rather a continuous, circular interaction that enriches scientific knowledge and supports methodological development in the study of human society